Decision support tools for agriculture: Towards effective design and delivery. (November 2016) - Rose, David C.; Sutherland, William J.; Parker, Caroline; Lobley, Matt; Winter, Michael; Morris, Carol; Twining, Susan; Ffoulkes, Charles; Amano, Tatsuya; Dicks, Lynn V.
Abstract: Decision support tools, usually considered to be software-based, may be an important part of the quest for evidence-based decision-making in agriculture to improve productivity and environmental outputs. These tools can lead users through clear steps and suggest optimal decision paths or may act more as information sources to improve the evidence base for decisions. Yet, despite their availability in a wide range of formats, studies in several countries have shown uptake to be disappointingly low. This paper uses a mixed methods approach to investigate the factors affecting the uptake and use of decision support tools by farmers and advisers in the UK. Through a combination of qualitative interviews and quantitative surveys, we found that fifteen factors are influential in convincing farmers and advisers to use decision support tools, which include usability, cost-effectiveness, performance, relevance to user, and compatibility with compliance demands. This study finds a plethora of agricultural decision support tools in operation in the UK, yet, like other studies, shows that their uptake is low. A better understanding of the fifteen factors identified should lead to more effective design and delivery of tools in the future. Highlights: A search of DST available for use by UK farmers and advisors found 395 tools 49% of farmers used some kind of decision support tool to inform decisions. All advisers used some form of decision support tools to inform decisions. Modes found most useful for farmers – software (28%), paper-based (22%), apps (10%). Fifteen characteristics were found to be influential for effective DST.